Upregulation of G Protein-Coupled Estrogen Receptor by Chrysin-Nanoparticles Inhibits Tumor Proliferation and Metastasis in Triple Negative Breast Cancer Xenograft Model - Kim, Kyoung Mee; Jung, Joohee (Frontiers in Endocrinology, 2020)
Triple-negative breast cancer (TNBC) is associated with a high mortality rate among women globally. TNBC shows a high rate of recurrence and distant metastasis. Particularly, the chemotherapy is limited because hormone therapy of breast cancer is ineffective. Thus, an effective chemotherapeutic agent is needed for tumor suppression. Chrysin-nanoparticles (chrysin-NPs) were investigated for their inhibitory effect on a MDA-MB-231-derived xenograft model. To gain insight into the underlying mechanisms, we conducted human matrix metalloproteinase (MMP) array, western blot, and immunohistochemistry analysis. Furthermore, in vivo imaging was used to monitor the chemotherapeutic efficacy of chrysin-NPs in a metastasis mouse model. Chrysin-NPs significantly inhibited the proliferation of MDA-MB-231 cells via the PI3K/JNK pathway and induced cell death through the p53-apoptosis pathway, leading to delayed MDA-MB-231-derived tumor growth. Interestingly, chrysin-NPs significantly induced G protein-coupled estrogen receptor (GPER) expression, which suppresses MMPs and NF-κB expression. Chrysin-NPs acted as effective metastasis inhibitors. Our results suggest that chrysin-NPs may be used as an effective adjuvant formulation to inhibit TNBC progression.